The Nature of Freedom - on the ethical potential of the knowledge of the non-human origins of human being - Hauberg-Lund, Martin (Res Cogitans, 2016)
Many ways there are to articulate the objective conditions of human subjectivity. If poetry is regarded as one way, philosophy ought to be regarded as another. Whereas young Danish poet Theis Ørntoft (1984-) in his Poems 2014invokes a host of metaphors inorder to stage and address the fluctuating and at most semi-stable foundations of human being, American philosopher Graham Harman (1968-) in his The Quadruple Objectexpounds the structural components of a metaphysics that uncovers the ontological relativity of the objectively secured stability of human subjectivity. The implications of Harman's so-called 'object-oriented ontology' for the ethically significant construal of the relation between nature and freedom will be spelled out towards the end of my article.